A population-based study on patients complaining regarding community pharmacies services - Marziyeh Zare; Saba Afifi; Iman Karimzadeh; Mohammad Salehi-Marzijarani; Leila Zarei; Gholamreza Ghazipour; Mahtabalsadat Mirjalili; Kamran B Lankarani; Ali Mohammad Sabzghabaee; Fariba Ahmadizar; Payam Peymani (Wolters Kluwer Medknow Publications, 2020)
Objective: Patients' complain regarding pharmaceutical services at community pharmacies is a fundamental issue as it can directly affect people's service utilization. For the first time in Iran, this survey aimed to investigate the experience of people regarding declare a complaint against the pharmacy sectors as a community-based study. Methods: In this cross-sectional study, over 100 samples based on postal codes were randomly selected from the city of Shiraz in 2017-2018. The data collection instrument was designed in two parts (demographic and social profile which record the complaint experiences against pharmacists, pharmacy services, etc.). The data were analyzed by SPSS. Findings: All 1035 eligible participants had a mean age of 45.54 ± 15.82 years (ranged from 14 to 91). Nearly 70% of the participants were female. Around 81.8% had a family physician coverage, whereas 7.4% of them had no medical insurance coverage. The frequency of complaints from the pharmacies was 35.6%. Nearly 55% of the complaints were related to governmental pharmacies. Homemakers were 1.36 times more likely to have experienced complaints in comparison with their employed female counterparts. Health status had an inverse association with complaints. Those participants who had received prescription medication were about two times more likely to have filed a complaint in comparison with those who received medication without a prescription. In addition, females aged 40-59 and above 60 and unemployed participants were more satisfied with respect to complaint follow-up process. Conclusion: Low level of satisfaction with respect to the complaint process is a concerning issue; hence, strategies are warranted to improve the quality of services provided in the pharmacies.